Contemporary human breath related topics: aerosols, saliva, and HR-MS bioinformatics from Pittcon 2019. (31st May 2019) - Pleil, Joachim D; Ariel Geer Wallace, M; Miekisch, Wolfram; DiFrancesco, Fabio
Abstract: Researchers from the International Association of Breath Research and the scientific board of the Journal of Breath Research (JBR) attended the annual Pittsburgh Conference and Exposition (Pittcon) in March 2019 in Philadelphia, PA, USA. Herein we report on a series of breath related topics from the meeting featuring sessions on exhaled breath aerosols and development of saliva analysis as a complement to non-invasive breath monitoring. Other contemporary breath related subjects, including bioinformatics, metabolomics, and forensics are also discussed.